The International Landscape of Medical Licensing Examinations: A Typology Derived From a Systematic Review - Tristan Price; Nick Lynn; Lee Coombes; Martin Roberts; Tom Gale; Sam Regan de Bere; Julian Archer (Kerman University of Medical Sciences, 2018)
Background National licensing examinations (NLEs) are large-scale examinations usually taken by medical doctors close to the point of graduation from medical school. Where NLEs are used, success is usually required to obtain a license for full practice. Approaches to national licensing, and the evidence that supports their use, varies significantly across the globe. This paper aims to develop a typology of NLEs, based on candidacy, to explore the implications of different examination types for workforce planning. Methods A systematic review of the published literature and medical licensing body websites, an electronic survey of all medical licensing bodies in highly developed nations, and a survey of medical regulators. Results The evidence gleaned through this systematic review highlights four approaches to NLEs: where graduating medical students wishing to practice in their national jurisdiction must pass a national licensing exam before they are granted a license to practice; where all prospective doctors, whether from the national jurisdiction or international medical graduates, are required to pass a national licensing exam in order to practice within that jurisdiction; where international medical graduates are required to pass a licensing exam if their qualifications are not acknowledged to be comparable with those students from the national jurisdiction; and where there are no NLEs in operation. This typology facilitates comparison across systems and highlights the implications of different licensing systems for workforce planning. Conclusion The issue of national licensing cannot be viewed in isolation from workforce planning; future research on the efficacy of national licensing systems to drive up standards should be integrated with research on the implications of such systems for the mobility of doctors to cross borders.